Análisis del proceso de evaluación al desempeño docente, aplicando técnicas de minería de datos. - Ortiz Pasaca, Janina Silvana (2014)
The great steps that technology gives nowadays, makes that there is increasing reliance on the use of systems exist and therefore the storage of data in all businesses or public or private entities. Within this large conglomerate of information generation the process of Teaching Performance Assessment plays an important role in the quality of higher education. Because, it is a process that seeks quality and academic excellence. The process of teaching performance assessment currently measures performance based on scores on the performance of teachers; going on a range of unsatisfactory at a very satisfactory level, although the student's opinion is collected, this only serves to reinforce the questions already established within a questionnaire, that is to say there is no process that evidences the views of students in improvement plan to the teacher evaluated. It also allowed the evolution of cathedra that had a teacher through the years, or the factors that influence a student when a teacher assesses. In this perspective the present titling work whose aim is to analyze the process of evaluation of teaching performance using data mining techniques to determine the degree of influence that the notes have of the students when evaluating a teacher, good performance or the existence of criteria of interest in the process and observing the evolution of cathedra that a teacher have in time. In addition to the application of data mining techniques made use of management tools and database mining tools. As for the performance of each process was based on the CRISP-DM methodology that allowed successfully completing each phase of mining. Data were obtained from the Telecommunications Unit and Information (UTI) in physical and through Web Services, note that the results of this research work can be used for suitable purposes or in support of decisions or optimization process.